(untitled) (Research, Society and Development, 2022)
Frailty syndrome is a multifactorial condition that results in clinical vulnerability and mortality. Objective: To verify the prevalence of frailty and associated factors among elderly users of a Basic Health Unit (UBS - Unidade básica de saúde). Method: Cross-sectional observational study with 354 elderly people from a UBS in Bahia. Data were obtained from medical records containing the Clinical-Functional Vulnerability Index and sociodemographic data. Statistical tools were used to analyse with descriptive, bivariate and multiple methods. Results: The elderly evaluated had a mean age of 72.4 years (SD 8.35), mostly self-declared black, women, with low level of education and living only with their spouse. There was a prevalence of frailty in 15.8% of the elderly, pre-frailty in 32.2% and robustness in 52%. A statistically relevant association was found between frailty and dependence for daily activities and multiple comorbidities. Frailty was more frequent among women, the elderly, those with low level of education, those living with other family members or just a spouse, and those with a negative self-perception of health. Conclusion: Recognizing the associated factors is essential for the development of effective policies for older people.